Energy-Efficient Paddy Rice Dehumidification using a Thermosyphon System - Poungthong, Pongthep; Promprasansuk, Sookjai; Tanaratchat, Vikorn; Promchai, Anuruk; Ritthong, Wirote (My University, 2025)
Efficient post-harvest drying is vital to maintain paddy rice quality, prevent spoilage, and extend storage life. This study presents a thermosyphon-based dehumidification system, tested with hot air and hot water heating at 60, 70, and 80 °C. The system includes a cylindrical drying chamber with automated controls for higher efficiency. Performance was evaluated using drying time, energy efficiency, and specific energy consumption (SEC). Results showed the system reduced paddy rice moisture from 26.65% to the target 14% (d.b.). Drying times with hot air were 128, 76, and 50 hours, while hot water required 104, 62, and 42 hours at 60, 70, and 80 °C, respectively. Hot water at 80°C achieved the fastest drying, completing the process in 42 hours. Energy performance analysis revealed the lowest SEC of 89.05 kWh/kg water for hot water at 80 °C, whereas hot air at 60 °C recorded the highest SEC of 1,204 kWh/kgwate. Overall, the thermosyphon system demonstrated strong potential for balancing drying speed and energy use. The study supports thermosyphon-based drying as a scalable, energy-efficient solution for post-harvest rice management, with hot water offering both rapid drying and efficiency
Keywords: Energy efficiency; Hotair drying; Hotwater drying; Paddyrice drying; Thermo syphon systems